Bi2La4O9, a monoclinic phase in the system Bi2O3-La2O3 - Chen, Xiaolong; Eysel, Walter; Li, J. Q. (Journal of solid state chemistry, 1996)
The binary system Bi2O3-La2O3with La2O3≥ 50 mole% has been investigated at 950-1000°C. The results revealed three compounds: Bi8La10O27, Bi2.4La3.6O9, and Bi2La4O9. Bi2.4La3.6O9has a rhombohedral subcell with hexagonal lattice parametersa= 3.96017(5) Å,c= 9.9691(2) Å, and space groupR3m. It is probably the same phase which was reported previously as Bi2La4O9(Refs. 5 and 6). Bi2La4O9has a monoclinic structure with the subcell lattice parametersa= 6.8290(3) Å,b= 3.9887(1) Å,c= 4.0524(1) Å and β = 125.094(3)° and subcell space groupC2/m. Its average structure has been determined by X-ray powder diffraction and refined by the Rietveld method. The average structure can be described as an oxygen deficient fluorite structure of the δ-Bi2O3type with La and Bi randomly distributed on the cation site. In addition, a superstructure has been observed by TEM.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Im Titel sind die Zahlen 2, 3, 4 und 9 tiefgestellt
Gesehen am 13.12.2022